2018
DOI: 10.1186/s12913-018-3397-y
|View full text |Cite
|
Sign up to set email alerts
|

‘Collective making’ as knowledge mobilisation: the contribution of participatory design in the co-creation of knowledge in healthcare

Abstract: The discourse in healthcare Knowledge Mobilisation (KMb) literature has shifted from simple, linear models of research knowledge production and action to more iterative and complex models. These aim to blend multiple stakeholders’ knowledge with research knowledge to address the research-practice gap. It has been suggested there is no ‘magic bullet’, but that a promising approach to take is knowledge co-creation in healthcare, particularly if a number of principles are applied. These include systems thinking, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
218
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 185 publications
(226 citation statements)
references
References 47 publications
3
218
0
5
Order By: Relevance
“…The explicit use of creative methods in coproduction addresses many of the challenges of coproduction, namely imbalances or deficits of power, language, trust, and time. It fosters an inclusive nonhierarchical environment [28] that allows all participants to be recognized as experts and produces results in the form of visible and tangible outputs owned by those who created them [29]. …”
Section: Methodsmentioning
confidence: 99%
“…The explicit use of creative methods in coproduction addresses many of the challenges of coproduction, namely imbalances or deficits of power, language, trust, and time. It fosters an inclusive nonhierarchical environment [28] that allows all participants to be recognized as experts and produces results in the form of visible and tangible outputs owned by those who created them [29]. …”
Section: Methodsmentioning
confidence: 99%
“…We adapted the interactive and participatory methodology described by previous authors. 29,37 Prior to the first workshop, we made large-scale diagrams of the different "best-in-class" frameworks from our systematic review and invited the groups to talk about them and use sticky notes to annotate them. We systematically captured and incorporated their suggestions for adaptation, and sought input from a professional design service to produce resources in multiple formats.…”
Section: Co-design Phasementioning
confidence: 99%
“…This literature includes reviews of approaches to co-creation of knowledge 102 and the sociology of design, 103 and (more specifically relevant to our empirical work) a recent theorization of "collective making." 29 In the last of these, Langley et al propose three domains of influence when people from different sectors come together to engage in creative play:…”
Section: Comparison With Other Studiesmentioning
confidence: 99%
“…We have found that co-creative practices, using design approaches can be helpful for power sharing. 12 One research theme, for example, developed a series of 'Getting Research into Practice'(GRiP) projects to work with clinical teams and services users on projects using co-creative design methods with them. Clinical teams applied to the CLAHRC to undertake a GRiP project The ACORN CoP aims to mobilise and develop knowledge around RCD within service provider organizations.…”
Section: Co-productionmentioning
confidence: 99%